The search for candidate genes associated with natural variation of grain Zn accumulation in barley. Issue 13 (2nd July 2019) - Detterbeck, Amelie; Nagel, Manuela; Rensch, Stefan; Weber, Michael; Börner, Andreas; Persson, Daniel P.; Schjoerring, Jan Kofod; Christov, Vesselin; Clemens, Stephan
Abstract : Combating hidden hunger through molecular breeding of nutritionally enriched crops requires a better understanding of micronutrient accumulation. We studied natural variation in grain micronutrient accumulation in barley ( Hordeum vulgare L.) and searched for candidate genes by assessing marker-trait associations (MTAs) and by analyzing transcriptional differences between low and high zinc (Zn) accumulating cultivars during grain filling. A collection of 180 barley lines was grown in three different environments. Our results show a pronounced variation in Zn accumulation, which was under strong genotype influence across different environments. Genome-wide association mapping revealed 13 shared MTAs. Across three environments, the most significantly associated marker was on chromosome 2H at 82.8 cM and in close vicinity to two yellow stripe like (YSL) genes. A subset of two pairs of lines with contrasting Zn accumulation was chosen for detailed analysis. Whole ears and flag leaves were analyzed 15 days after pollination to detect transcriptional differences associated with elevated Zn concentrations in the grain. A putative α-amylase/trypsin inhibitor CMb precursor was decidedly higher expressed in high Zn cultivars in whole ears in all comparisons. Additionally, a gene similar to barley metal tolerance protein 5 ( MTP5 ) was found to be a potential candidate gene.